2021
DOI: 10.3390/ma14143964
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Metastable Silicon Allotropes

Abstract: Diamond cubic silicon is widely used for electronic applications, integrated circuits, and photovoltaics, due to its high abundance, nontoxicity, and outstanding physicochemical properties. However, it is a semiconductor with an indirect band gap, depriving its further development. Fortunately, other polymorphs of silicon have been discovered successfully, and new functional allotropes are continuing to emerge, some of which are even stable in ambient conditions and could form the basis for the next revolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Silicon (Si) as a key material in semiconductors and nanoelectronics, has drawn extensive attention for several decades. , Diamond cubic Si (Si-I, space group Fd 3̅ m ) along with its fundamental properties have been well investigated under ambient condition. Extreme conditions, such as hydrostatic pressure, can arouse numerous phase transitions, discover extraordinary Si structures, and may further stimulate practical applications. High-pressure studies on Si started more than 60 years ago, and since then plenty of novel Si allotropes have been reported by using diamond anvil cells (DAC). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) as a key material in semiconductors and nanoelectronics, has drawn extensive attention for several decades. , Diamond cubic Si (Si-I, space group Fd 3̅ m ) along with its fundamental properties have been well investigated under ambient condition. Extreme conditions, such as hydrostatic pressure, can arouse numerous phase transitions, discover extraordinary Si structures, and may further stimulate practical applications. High-pressure studies on Si started more than 60 years ago, and since then plenty of novel Si allotropes have been reported by using diamond anvil cells (DAC). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) is a highly versatile material that has found promising applications in various modern technologies, including battery anodes, 1-3 solar cells, [4][5][6] microelectromechanical systems (MEMS), 7,8 transistors, 9,10 and thermoelectric harvesters, due to its unique properties and advantages such as geoabundance, good engineering, low-cost production, nontoxicity, and so forth. [11][12][13] Recently, it was revealed that Si has tunable properties as its dimensionality is reduced, unlocking more opportunities for advanced technical applications. For instance, it was reported that two-dimensional (2D) Si structures can serve as high-performance anode materials for lithium ion (Li + ) batteries because their lithium intercalating capacity (42100 mA h g À1 ) surpasses that of 0D Si structures.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) shapes our present-day technologies in battery anodes [1][2][3], solar cells [4][5][6], microelectromechanical * Authors to whom any correspondence should be addressed. systems (MEMS) [7,8], transistor [9,10], and thermoelectric harvesters because of its unique properties, as well as geoabundance, good engineering and low-cost production, nontoxicity, and so forth [11][12][13]. It is worth noting that, with the reduction in the dimensionality, the properties of Si are sharply changed, enabling more possibilities in its advanced technical applications.…”
Section: Introductionmentioning
confidence: 99%